2009
DOI: 10.1117/12.818332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hokuyo URG-04LX laser rangefinder for mobile robot obstacle negotiation

Abstract: This paper presents a characterization study of the Hokuyo URG-04LX scanning laser rangefinder (LRF). The Hokuyo LRF is similar in function to the Sick LRF, which has been the de-facto standard range sensor for mobile robot obstacle avoidance and mapping applications for the last decade. Problems with the Sick LRF are its relatively large size, weight, and power consumption, allowing its use only on relatively large mobile robots. The Hokuyo LRF is substantially smaller, lighter, and consumes less power, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 15 publications
3
62
0
Order By: Relevance
“…3, No. 6, November 2014 performance and characteristic of Hokuyo URG-04LX-UG01 is almost the same with the performance of URG-04LX that has been reviewed its characteristics by [6], [7]. They said, URG-04LX output performance need 90 minutes to stable.…”
Section: Hokuyo Urg Seriesmentioning
confidence: 73%
“…3, No. 6, November 2014 performance and characteristic of Hokuyo URG-04LX-UG01 is almost the same with the performance of URG-04LX that has been reviewed its characteristics by [6], [7]. They said, URG-04LX output performance need 90 minutes to stable.…”
Section: Hokuyo Urg Seriesmentioning
confidence: 73%
“…3). After deletion of isolated points caused by a mixed pixel phenomenon [10], which generates a measured range resulting from a combination of the foreground and the background objects, we cluster the scan points using simple nearest neighbor classification by moving a sliding window of a 3-point size and discerning the separated objects using a minimal Euclidean distance threshold. The thresholds are highly implementation dependent, in our case are T sec = 20, T max sel = 200 and T min sel = 20.…”
Section: Data Clustering and Selectionmentioning
confidence: 99%
“…Table 3 shows the results the indoor experimental studies conducted using the autonomous hexarotor shown in Figure 7. Observations were gathered using the onboard laser range finder, Hokuyo UR04-LX [21] Considering the results of the experiments on ATE, it can be concluded that a UAV can navigate and localize successfully using its onboard sensors and a preloaded map when collecting metering data in rural areas. Also, as shown in Table 3, it is observed that increasing the UAV's speed increases ATE and reduces accuracy.…”
Section: An Evaluation On the Accuracy Of Navigation And Localizationmentioning
confidence: 99%